PENGARUH METODE RECIPROCAL LEARNING TERHADAP HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN DI SMA NEGERI 1 SIMPANG DUA KETAPANG - Hemafitria, Hemafitria; Octavia, Erna; Mitiana, Mitiana (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2023)
The aim of this research is to obtain information on the influence of the application of the reciprocal learning method on student learning outcomes in citizenship education subjects in class XI of SMA Negeri 1 Simpang Dua, Ketapang Regency.The research method used in this research is experimentation in the form of Pre-Experimental Design. From the results of data analysis, it can be concluded that there is an influence of the application of the reciprocal learning method on student learning outcomes in citizenship education subjects in class XI of SMA Negeri 1 Simpang Dua, Ketapang Regency.The results of the research after being given the reciprocal learning method, obtained data from research samples with a sample size of 28, the average value is 70.00, the middle value is 70.00, the value that often appears is 70.00, the difference value between the maximum and minimum namely 20.00, the lowest value is 60.00, the highest value is 80.00, the total value is 1960. The results of the research before being given the reciprocal learning method, obtained data from research samples with a total sample of 28, the average value is 87.85, the middle value is 90.00, the value that often appears is 90.00, the difference between the maximum and minimum value is 15.00, the lowest value is 80.00, the highest (maximum) value is 95.00, the total value The total is 2460. So it can be concluded that the student's score after using the reciprocal learning method is higher than before using the reciprocal learning method. This can be seen from the difference in the average learning outcomes of class.